2019
DOI: 10.1021/acs.macromol.9b02008
|View full text |Cite
|
Sign up to set email alerts
|

Facial Amphiphilicity-Induced Self-Assembly (FAISA) of Amphiphilic Copolymers

Abstract: Amphiphilic molecules, including macromolecules and small surfactants, inherently self-assemble into a wide variety of nanostructures in selective solvents. However, the sequential structure for synthetic polymers is largely restricted to block copolymers. In this work, we report facial amphiphilicity-induced self-assembly (FAISA) of gradient amphiphilic copolymers. This new approach is demonstrated using facial amphiphilic multicyclic compounds. The facial amphiphilicity of bile acids allows cationic copolyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…Moreover, a class of BA-based antibiotics termed Ceragenins have been prepared by covalently attaching amines to BAs, inspired by the molecular structure of squalamine, a naturally occurring aminosterol with potent antimicrobial activity, isolated from shark liver [ 101 , 102 , 103 ]. Similar molecules have been linked as pendants to polymers able to locally cluster the facial amphiphilicity of these cationic steroid antibiotics, thereby enhancing interactions with bacterial membranes [ 104 , 105 , 106 ] ( Figure 3 g–i). To date, BAs are actually used both as precursor and co-agent in drug formulation.…”
Section: Functionalized Bas In Medicinementioning
confidence: 99%
“…Moreover, a class of BA-based antibiotics termed Ceragenins have been prepared by covalently attaching amines to BAs, inspired by the molecular structure of squalamine, a naturally occurring aminosterol with potent antimicrobial activity, isolated from shark liver [ 101 , 102 , 103 ]. Similar molecules have been linked as pendants to polymers able to locally cluster the facial amphiphilicity of these cationic steroid antibiotics, thereby enhancing interactions with bacterial membranes [ 104 , 105 , 106 ] ( Figure 3 g–i). To date, BAs are actually used both as precursor and co-agent in drug formulation.…”
Section: Functionalized Bas In Medicinementioning
confidence: 99%
“…Rahman et al 189 synthesized random and block copolymers of OEGMA and bile acid methacrylic derivatives to explore the effect of hydrophobic interactions, charge density and monomers distribution on aggregation induced by facial amphiphilicity‐induced self‐assembly (FAISA). The Authors also showed that the aggregates respond to temperature and ion screening.…”
Section: Study‐through‐synthesis Approach In Msr Copolymersmentioning
confidence: 99%
“…54−56 Recently, the literature has reported antibacterial polymers bearing quaternary ammonium decorated BA pendants, and these polymeric antibacterials are endowed with durable antibacterial property and hypotoxicity. 36,32,57,58 Some steroid−amino acid conjugates and some bile acid−bioactive molecule conjugates have been reviewed in the applications of medicinal chemistry and material science, 59,60 but there is no specific review to summarize the recent progress in bile acidbased antimicrobials. Herein, this review puts an emphasis on the role of BAs in development of antimicrobials classified by the number of BA units, including unimolecular, oligomeric, and macromolecular antimicrobials.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the past decades, through utilizing facial amphiphilic structures of BAs, there have been extensive efforts in the development of bile acid-based antimicrobials in which BA skeletons were conjugated with some positive segments, such as primary amine and quaternary ammonium. For example, Savage and co-workers developed a series of ceragenins to mimic cationic, facial amphiphilic structures of most AMPs by the use of a BA scaffold and appended amine groups. Recently, the literature has reported antibacterial polymers bearing quaternary ammonium decorated BA pendants, and these polymeric antibacterials are endowed with durable antibacterial property and hypotoxicity. ,,, Some steroid–amino acid conjugates and some bile acid–bioactive molecule conjugates have been reviewed in the applications of medicinal chemistry and material science, , but there is no specific review to summarize the recent progress in bile acid-based antimicrobials. Herein, this review puts an emphasis on the role of BAs in development of antimicrobials classified by the number of BA units, including unimolecular, oligomeric, and macromolecular antimicrobials.…”
Section: Introductionmentioning
confidence: 99%